The uppermost Cretaceous continental deposits at the southern end of Patagonia, the Chorrillo Formation case study (Austral-Magallanes Basin): Sedimentology, fossil content and regional implications. (February 2022) - Moyano-Paz, D.; Rozadilla, S.; Agnolín, F.; Vera, E.; Coronel, M.D.; Varela, A.N.; Gómez-Dacal, A.R.; Aranciaga-Rolando, A.M.; D'Angelo, J.; Pérez-Loinaze, V.; Richiano, S.; Chimento, N.; et al.
Abstract: The deposits of the Chorrillo Formation (Maastrichtian) were accumulated during a 'continental window' that occurred during the Late Cretaceous in the Austral-Magallanes foreland basin, southern Patagonia, Argentina. The aim of the present contribution is to describe the depositional conditions as well as new vertebrate and plant fossils from this unit. The analysis of these deposits resulted in the definition of five architectural elements: Complex sandy narrow sheets channels (SS), Complex gravelly narrow sheets channels (GS), Sandstone lobes (SL), Thick fine-grained deposits (GF) and Thin dark fine-grained deposits (DF). These were separated into channelized and non-channelized units and represent the accumulation in a fine-grained dominated, fossil rich fluvial depositional system. Vertebrates fossil records include two species of frogs of the genus Calypteocephalella (representing the southernmost record of Pipoidea), snakes belonging to Madtsoiidae and Anilioidea (the latter ones being the first records for the basin), chelid turtles similar to Yaminuechelys - Hydromedusa, meiolaniiform turtles, titanosaur sauropods, megaraptoran theropods, new remains of the elasmarian Isasicursor santacrucensis (including the first cranial remains available for this species), hadrosaur ornithischians, enantiornithine birds. Sharks and elasmosaurs are also recorded and may possibly derive from the overlying marine Calafate Formation. These new taxa, together with previous findings from the Chorrillo Formation, are included into a stratigraphic column, thus providing valuable information that sheds new light on faunistic composition and paleobiogeography of high-latitude biotas of Gondwana. Highlights: The depositional architectural elements and the paleontological content from the Chorrillo Formation are described. The Chorrillo Formation is interpreted as accumulated in a fluvial depositional system dominated by fine-grained deposits. The continentalization of the basin provided new ecological niches for plants and vertebrates. The fossil vertebrates association matches with the one reported from the Dorotea Formation.